A perspective on galactose-based fermentative hydrogen production from macroalgal biomass: Trends and opportunities. (May 2019) - Kim, Sang-Hyoun; Mudhoo, Ackmez; Pugazhendhi, Arivalagan; Saratale, Rijuta Ganesh; Surroop, Dinesh; Jeetah, Pratima; Park, Jeong-Hoon; Saratale, Ganesh Dattatraya; Kumar, Gopalakrishnan
Graphical abstract: Highlights: Macroalgae-based galactose can be harnessed as substrate for hydrogen synthesis. Galactose-to-H2 by fermentation is highly successful at academic research level. Hydrogen from galactose by fermentation holds promise as a source of bioenergy. Process intensification of galactose-to-H2 fermentation is a current challenge. Supply chain for macroalgae-based galactose-to-H2 needs in-depth analysis. Abstract: This review analyses the relevant studies which focused on hydrogen synthesis by dark fermentation of galactose from macroalgal biomass by discussing the inoculum-related pretreatments, batch fermentation and inhibition, continuous fermentation systems, bioreactor designs for continuous operation and ionic liquid-assisted catalysis. The potential for process development is also revisited and the challenges towards suppressing glucose dominance over a galactose-based hydrogen production system are presented. The key challenges in the pretreatment process aiming to achieve a maximum recovery of upgradable (fermentable) sugars from the hydrolysates and promoting the concomitant detoxification of the hydrolysates have also been highlighted. The research avenues for bioprocess intensification connected to enhance selective sugar recovery and effective detoxification constitute the critical steps to develop future red macroalgae-derived galactose-based robust biohydrogen production system.